Perceived Overqualification and Job Crafting: The Mediating Role of Workplace Anxiety and Moderating Role of Reappraisal - Zhang, Wei; Yan, Zhaoyi; Wang, Bin; Qu, Yi; Qian, Jing (SAGE Publications Inc., 2022)
Existing research has indicated the direct effect of perceived overqualification on job crafting,but little is known about the underlying mechanisms and processes through which this occurs. Drawing on motivation and capability-based approaches,we proposed and examined how employees’ perception of their overqualification would influence job crafting by increasing workplace anxiety. Furthermore,we employ emotion regulation literature to predict that reappraisal will mitigate the negative effects of workplace anxiety on job crafting. Using a sample of 1,112 workers from China,our findings showed that (1) perceived overqualification was positively associated with job crafting; (2) perceived overqualification was positively associated with workplace anxiety,which in turn reduced job crafting; and (3) reappraisal emotion regulation weakened the detrimental effect of workplace anxiety on job crafting. Based on these findings,we discussed theoretical and practical implications. © The Author(s) 2022.
Keywords: Job crafting; Perceived overqualification; Reappraisal emotion regulation; Motivation and capability-based approaches; Workplace anxiety; ODS 8 - Trabajo decente y crecimiento económico